Age estimation by measurement of open apices in tooth roots: Study using Saudi Arabian samples. (February 2019) - AlShahrani, Ibrahim; Yassin, Syed M.; Togoo, Rafi Ahmed; Tikare, Shreyas; Khader, Mohasin Abdul; Alkahtani, Zuhair M.
Abstract: The aim of this study was to verify Cameriere's regression formula to predict chronologic age in Saudi Population and if proven to be inaccurate, develop a new algorithm specific for Saudi children. A total of 788 Orthopantamographs(495 boys and 293 girls) were analyzed. The tooth measurement parameters were: number of teeth with closed apex ( N 0 ), open apex width ( a ), crown length ( l ), A/L ratio for each tooth ( x 1 to x 7 ) and summation of all open apex width ( s ). The radiographic measurements were substituted in the formula: Age = 8.971 + 0.375 g  + 1.631 x 5 + 0.674 N 0 – 1.034s–0.176s * N 0 The mean dental age assessed by Cameriere's method was significantly lower than chronologic age in Saudi population and with both genders and total study population (p < 0.05). A stepwise linear regression showed all parameters gender, N 0, x 1 to x 7 except x 2 significantly associated with age (R 2  = 0.6334, F (6, 779) = 168.28, p < 0.05). There was no statistically significant difference between predicted and actual chronologic age for 788 children using regression equation for Saudi population (p = 1). Cameriere's formula verified in Saudi children was found to underestimate the chronologic age in both genders. A prediction formula based on Cameriere's method specific to Saudi children has been developed for estimating chronologic age. The new regression formula developed will be more accurate for age assessment in Saudi children. Highlights: Cameriere's formula (2006) underestimated chronologic age in Saudi population. Mean age difference was 0.25 ± 1.29 in girls and 0.26 ± 1.57 years in boys. New regression formula is specific to Saudi population.